Concentrations of HCG Hormone in Urine by Optical means (Journal of the College of Basic Education, 2023)
Human chorionic Gonadotropin (HCG) in the urine of pregnantwomen, this in addition to the standard samples. Fluorescence testsresults showed good compatibility with those of the radioimmunologyassay tests, as a prominent peak appeared in the curve of the fluorescenceintensity at the wavelength 475 nanometer in the urine samples duringpregnancy.